Financing electoral campaigns according to the 21/01 organic law relating to electoral system. - Ghaoues, Hassina (Journal of Human Sciences, 2022)
Financing elections has  a great importance.It is a fundemental factor which  can guide the results in  favor  of some members or  political  parties rather than others.This is illegal and illegitimate .Therefore,for fear of resorting  to illegal financial sources ,and in  order to  avoid suspicious fina,cing  and  the  use of corrupt  money  in  the  elections, the legislator,along  the   lines  of comparative legislation, reconsidered the financing of electoral  campain in accordance with organic law 21/01  to  strict legislative regulation and  strict control, and  the installation of a special  committee to remove corrupt money from politics  and to ensure  the  principle of  equality and equal opportunities for all candidates.